2010
DOI: 10.4103/0019-5049.63659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clonidine and magnesium sulphate on anaesthetic consumption, haemodynamics and postoperative recovery: A comparative study

Abstract: This randomised, placebo-controlled, double-blind study was designed to assess the effect of intravenous clonidine and magnesium sulphate on intraoperative haemodynamics, anaesthetic consumption and postoperative recovery. Seventy five patients undergoing elective upper limb orthopaedic surgery were randomised into three groups. Group C received clonidine 3 μg/kg as a bolus before induction and 1μg/kg/hour by infusion intraopertively. Group M received magnesium sulphate 30 mg/kg as a bolus before induction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…These results agree with previous studies [7,9] as well as with Singh and Arora [10] concerning clonidine.…”
Section: Discussionsupporting
confidence: 94%
“…These results agree with previous studies [7,9] as well as with Singh and Arora [10] concerning clonidine.…”
Section: Discussionsupporting
confidence: 94%
“…[ 25 ] Similarly, the preoperative infusion of MgSO 4 also reduced the anesthetic demands and the time needed to reach a BIS value of 60. [ 26 27 ] BIS-guided general anesthesia reduced the exposure time and doses, causing a reduction in neurotoxicity and expedited recovery from anesthesia because sedation produced by dexmedetomidine and MgSO 4 helped to achieve the target BIS range earlier and with reduced dose of propofol. BIS has shown to reduce the risk of developing delirium during initial hospitalization and postoperative cognitive dysfunction at 3 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the intraoperative use of MgSO 4 caused delayed recovery, which may be related to dosage protocol used in their study. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%